2011
DOI: 10.1124/mol.111.071027
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Labeling of Brain Capillary Endothelial Cells after Intravenous Injection of Monoclonal Antibodies Targeting the Transferrin Receptor

Abstract: The development of vectors for drug delivery to the central nervous system remains a major pharmaceutical challenge. Here, we have characterized the brain distribution of two monoclonal antibodies (MAbs) targeting the mouse transferrin receptor (TfR) (clones Ri7 and 8D3) compared with control IgGs after intravenous injection into mice. MAbs were fluorolabeled with either Alexa Fluor (AF) dyes 647 or 750. Intravenous injection of Ri7 or 8D3 MAb coupled with AF750 led to higher fluorescence emission in brain hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
65
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 37 publications
8
65
0
Order By: Relevance
“…Other targets that have been used for BBB-targeting of siRNA include the insulin receptor [104], and the LDL receptor [105]. Transferrin receptor targeted delivery has shown some success for protein and drug uptake into the brain [102,106] but in other cases, trapping in the brain microvasculature has been reported [107,108]. Recently, a more detailed insight into the mechanisms has revealed that the affinity (or avidity) of the peptide or protein ligand to the transferrin receptor is crucial in deciding the fate [103,106,109].…”
Section: Targets and Ligands For Bbb Transcytosismentioning
confidence: 98%
“…Other targets that have been used for BBB-targeting of siRNA include the insulin receptor [104], and the LDL receptor [105]. Transferrin receptor targeted delivery has shown some success for protein and drug uptake into the brain [102,106] but in other cases, trapping in the brain microvasculature has been reported [107,108]. Recently, a more detailed insight into the mechanisms has revealed that the affinity (or avidity) of the peptide or protein ligand to the transferrin receptor is crucial in deciding the fate [103,106,109].…”
Section: Targets and Ligands For Bbb Transcytosismentioning
confidence: 98%
“…Indeed, IVIg is a heterogeneous product representative of the hIgG repertoire of thousands of healthy donors 5 with highly variable amino-acid composition. 33 Thus, a fraction of these IgG molecules may cross the BBB because of characteristics such as their isoelectric point, 34 degree of hydrophobicity, amino-acid composition, or antigen specificity, 31 whereas the majority might be excluded from the brain. Thus, our data underscore the possibility that deciphering the characteristics of IVIg molecules that allows their migration into the CNS as well as the transporters involved could lead to the identification of brain-penetrant IgG and to the optimization of IVIg use in prevalent CNS disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that IgG binding to transferrin or insulin receptors can access brain cells by mimicking their normal substrates. 31 This strategy was used to engineer chimeric antibodies to promote blood-to-brain transport of therapeutic (A and B) Nontransgenic (NonTg) and 3xTg-AD mice received three injections of IVIg (subchronic treatment) or equivalent volumes of vehicle (Ctrl) and were perfused with 50 mL phosphate-buffered saline (PBS) buffer followed with 50 mL 4% paraformaldehyde. Representative (A) immunohistochemistry and (B) immunofluorescent labeling of IVIg on 35-mm-thick brain sections of 4-to 9-month-old 3xTg-AD and NonTg mice (4-8 animals per group).…”
Section: Discussionmentioning
confidence: 99%
“…Bivalent binding can induce dimerization or higher order oligomerization of the receptor at the cell surface and/or inside the cell and is likely to change the natural arrangement and density of the receptor. Interestingly, recent studies showed that bivalent binding of an antibody to its cognate receptor leads to trapping of the antibody inside the brain endothelial cells of the BBB [11,12]. Consequently, the fraction of the antibody that actually gets through the BBB and into the brain parenchyma is very small.…”
mentioning
confidence: 99%